Delayed diagnosis of 22q11 deletion syndrome due to late onset hypocalcemia in a 11-year-old girl with imperforated anus - Dong-Yoon Yoo; Hae Jung Kim; Kee Hyun Cho; Eun Byul Kwon; Eun-Gyong Yoo (Korean Society of Pediatric Endocrinology, 2017)
Neonatal hypocalcemia and congenital heart defects has been known as the first clinical manifestation of the chromosome 22q11.2 deletion syndrome (22q11DS). However, because of its wide clinical spectrum, diagnosis of 22q11DS can be delayed in children without classic symptoms. We report the case of a girl with the history of imperforate anus but without neonatal hypocalcemia or major cardiac anomaly, who was diagnosed for 22q11DS at the age of 11 after the onset of overt hypocalcemia. She was born uneventfully from phenotypically normal Korean parents. Imperforate anus and partial cleft palate were found at birth, which were surgically repaired thereafter. There was no history of neonatal hypocalcemia, and karyotyping by GTG banding was normal. At the age of 11, hypocalcemia (serum calcium, 5.0 mg/dL) and decreased parathyroid hormone level (10.8 pg/mL) was noted when she visited our Emergency Department for fever and vomiting. The 22q11DS was suspected because of her mild mental retardation and velopharyngeal insufficiency, and a microdeletion on chromosome 22q11.2 was confirmed by fluorescence in situ hybridization. The 22q11DS should be considered in the differential diagnosis of hypocalcemia at any age because of its wide clinical spectrum.